2015
DOI: 10.1186/s12943-015-0368-3
|View full text |Cite
|
Sign up to set email alerts
|

The homeoprotein DLX4 controls inducible nitric oxide synthase-mediated angiogenesis in ovarian cancer

Abstract: BackgroundHomeobox genes encode transcription factors that control patterning of virtually all organ systems including the vasculature. Tumor angiogenesis is stimulated by several homeobox genes that are overexpressed in tumor cells, but the mechanisms of these genes are poorly understood. In this study, we investigated the mechanisms by which DLX4, a homeobox gene that is associated with increased tumor microvessel density, stimulates ovarian tumor angiogenesis.MethodsExpression of DLX4 and nitric oxide synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Therefore, we evaluated STAT1 activation in order to explore the underlying mechanism of IL-17-mediated upregulation of NOS2 induced by IFN-γ. Previous research has shown that Tyr701-p-STAT1 is pivotal in STAT1-dependent regulation of NOS2 expression ( 21 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we evaluated STAT1 activation in order to explore the underlying mechanism of IL-17-mediated upregulation of NOS2 induced by IFN-γ. Previous research has shown that Tyr701-p-STAT1 is pivotal in STAT1-dependent regulation of NOS2 expression ( 21 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In metastases, c-Fos and Fos B expression were significantly lower than in the respective primary OC tissues, which also indicated that FOS might be a potential cancer suppressor gene [24]. Trinh B. revealed that STAT1 could interact with DLX4 and promote ovarian tumor angiogenesis in part by stimulating iNOS expression [25]. STAT1 was found overexpressed in patients with high-grade serous OC after the development of clinical platinum resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The gene can drive tumor progression in ovarian cancer through the NF-κB pathway by activating a regulatory factor cell surface molecule CD44 [32]. It was also found to promote ovarian cancer by inducing the expression of iNOS, an enzyme that stimulates angiogenesis [33].…”
Section: Discussionmentioning
confidence: 99%